2012
DOI: 10.1055/s-0031-1300960
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Mandibular Distraction Osteogenesis in the Neonate with Pierre Robin Sequence and Airway Obstruction: A Primary Option

Abstract: Children with craniofacial abnormalities associated with retromicrognathia and glossoptosis often have compromised upper airway flow. In severe cases, emergency intubation is necessary immediately after birth, and tracheostomy is advocated to manage the airway in the neonatal period and to allow for feeding. Early intervention with bilateral mandibular osteogenesis avoids the need for tracheostomy, along with its complications, and it targets the primary etiologic factor of the problem—the anomalous anatomy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…One of the complications with the greatest description in the literature is dental injuries, reported by Zenha et al 23 After an exhaustive review of the literature, we found no reports on complications of the salivary glands with the use of mandibular distractors. For this reason, we described these 2 cases, never described before in medical literature, relating clinical management, covering all differential diagnoses, and complications associated with the use of bone distractors.…”
Section: Discussionmentioning
confidence: 63%
“…One of the complications with the greatest description in the literature is dental injuries, reported by Zenha et al 23 After an exhaustive review of the literature, we found no reports on complications of the salivary glands with the use of mandibular distractors. For this reason, we described these 2 cases, never described before in medical literature, relating clinical management, covering all differential diagnoses, and complications associated with the use of bone distractors.…”
Section: Discussionmentioning
confidence: 63%
“…Longer-term dental outcomes were reported by Zenha et al 39 Two patients with RS underwent neonatal MDO with 2 and 6 years of follow-up. The 6-year-old patient was found to have normal tooth eruption.…”
Section: Discussionmentioning
confidence: 81%
“…[37][38][39] Many authors have reported excellent outcomes of MDO, effectively relieving obstructive sleep apnea and preventing tracheostomies in up to 90 to 100% of children with micrognathia or retrognathia. 34,[40][41][42][43][44][45][46] In addition, MDO has been shown to be effective in terms of facilitating decannulation in tracheostomydependent children with severe micrognathia. 47 Although MDO is generally accepted as a safe and effective treatment modality in this patient population, the significant potential consequences of procedural failure highlight the importance of preoperatively identifying predictors of failure, thus avoiding unnecessary major surgery and possibly reducing the mortality rate.…”
Section: Discussionmentioning
confidence: 99%